Direct detection of falciparum and non-falciparum malaria DNA from a drop of blood with high sensitivity by the dried-LAMP system. Issue 1 (December 2017) - Hayashida, Kyoko; Kajino, Kiichi; Simukoko, Humphrey; Simuunza, Martin; Ndebe, Joseph; Chota, Amos; Namangala, Boniface; Sugimoto, Chihiro
Abstract Background Because of the low sensitivity of conventional rapid diagnostic tests (RDTs) for malaria infections, the actual prevalence of the diseases, especially those caused by non-Plasmodium falciparum (non-Pf) species, in asymptomatic populations remain less defined in countries lacking in well-equipped facilities for accurate diagnoses. Our direct blood dry LAMP system (CZC-LAMP) was applied to the diagnosis of malaria as simple, rapid and highly sensitive method as an alternative for conventional RDTs in malaria endemic areas where laboratory resources are limited. Results LAMP primer sets for mitochondria DNAs ofPlasmodium falciparum (Pf) and human-infective species other than Pf (non-Pf;P. vivax, P. ovale, P. malariae ) were designed and tested by using human blood DNA samples from 74 residents from a malaria endemic area in eastern Zambia. These malaria dry-LAMPs were optimized for field or point-of-care operations, and evaluated in the field at a malaria endemic area in Zambia with 96 human blood samples. To determine the sensitivities and specificities, results obtained by the on-site LAMP diagnosis were compared with those by the nested PCR and nucleotide sequencing of its product. The dry LAMPs showed the sensitivities of 89.7% for Pf and 85.7% for non-Pf, and the specificities of 97.2% for Pf and 100% for non-Pf, with purified blood DNA samples. The direct blood LAMP diagnostic methods, in which 1 μl of anticoagulated blood were used as the template, showed the sensitivities of 98.1% for Pf, 92.1% for non-Pf, and the specificities of 98.1% for Pf, 100% for non-Pf. The prevalences ofP. falciparum, P. malariae andP. ovale in the surveyed area were 52.4, 25.3 and 10.6%, respectively, indicating high prevalence of asymptomatic carriers in endemic areas in Zambia. Conclusions We have developed new field-applicable malaria diagnostic tests. The malaria CZC-LAMPs showed high sensitivity and specificity to bothP. falciparum and non-P. falciparum . These malaria CZC-LAMPs provide new means for rapid, sensitive and reliable point-of-care diagnosis for low-density malaria infections, and are expected to help update current knowledge of malaria epidemiology, and can contribute to the elimination of malaria from endemic areas.